Reduzibilität eines Systems der Differentialgleichungen mit fastperiodischen Koeffizienten - Merkys, V. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. М. Меркис. О приводимости одной системы дифференциальных уравнений с почти-периодическими коэффициентами V. Merkys. Vienos diferencialinių lygčių sistemos su beveik periodiniais koeficientais redukavimas